Narrativity and intertextuality in the Ayacucho tradition "Helme" - Felices Morales, Rina Lilibet (2024)
The Helme tradition, belongs to the Ayacucho popular oral literature, has gradually spread. The objective of this article is to demonstrate that diachronically, its narrative structure and intertextuality were consolidated with a polygeneric corpus; through the sensitive pen of the writers who were building it in written form. Due to the nature of this (literary) research, the following are taken into account: perspectives, opinions, meanings, and assessment of the narrativity and intertextuality found in the books of the Helme tradition, written by different authors. Statistical work is not taken into account. Due to the existence of the patriarchy, Rosa, a beautiful young woman, is forced to marry a man much older than her. It results in a tragic passional triangle. In conclusion, this study results in being a contribution to the consolidation of Ayacucho literature from the narrativity and intertextuality linked to the strengthening of tradition.